Photodynamic Therapy for the Treatment of Complex Anal Fistula. Issue 6 (19th September 2019) - Arroyo, Antonio; Sánchez‐Guillén, Luis; Parra, Pedro Antonio; García‐Catalá, Luis; Peña‐Ros, Emilio; Ferrer‐Márquez, Manuel; Nofuentes Riera, Carmen; Barber‐Valles, Xavier; Romero‐Simó, Manuel
Abstract : Background and Objectives: To validate and analyze the results of intralesional photodynamic therapy in the treatment of complex anal fistula. Study Design/Materials and Methods: This prospective multicentric observational study enrolled patients treated for complex anal fistula who underwent intralesional photodynamic therapy (i‐PDT). The included patients were treated from January 2016 to December 2018 with a minimum follow‐up of 1 year to evaluate recurrence, continence and postoperative morbidity. Intralesional 5‐aminolevulinic acid (ALA) gel (2%) was injected directly into the fistula. The internal and external orifices were closed. After an incubation period of 2 hours, the fistula was irradiated using an optical fiber connected to a red laser (Multidiode 630 PDT) operating at 1 W/cm for 3 minutes (180 J). Results: In total, 49 patients were included (61.2% male). The mean age was 48 years, and the mean duration of fistula was 13 months. Of the fistulas included, 75.5% were medium transphincteric, and 24.5% were high transphincteric. The median fistula length was 4 ± 1, 14 cm (range: 3–5). A total of 41 patients (83.7%) had a previous history of fistula surgery. Preoperatively, some degree of anal incontinence was found in 5 patients (10.2%). No center reported any other procedure‐related complications intraoperatively. Phototoxicity was found in one patient. In the first 48 hours after the procedure, fever was reported in 2 patients (4%). At the end of follow‐up, total healing was observed in 32/49 patients (65.3%). No patient reported new incontinence postoperatively. Conclusion: i‐PDT could be considered a good choice in patients with complex anal fistulas to avoid surgery and its complications. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.